Korelasi pendapatan dengan tinggi badan anak baru masuk sekolah (tbabs - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Abstract This study investigates the relationship between household economic variables with standardized height-for-age of early scholl children in two rural setting and one urban areas in West Sumatera. Height of 474 earlier school children were measured and mothers were interviewed. The study confirms positive relationship between household economic variables with child height with different degree of significant. The evidences also support that height-for-age of earlier school children can be viewed as nutritional outcome as well as development achivement. Keywords: household economic